Pengembangan Media Pembelajaran Scratch untuk Meningkatkan Pemahaman Angka dan Bentuk Anak Usia Dini di Nabire - Ester Ayuk Pusvita; Natalia Natalia; Arief Rahman Hakim (Lembaga Pengembangan Kinerja Dosen, 2025)
Low interest and understanding of basic mathematics among children due to the use of conventional methods that are monotonous and uninteresting, as well as limited access to innovative learning media and human resources trained in modern teaching methods, also exacerbate this condition, creating a gap between the expected curriculum and its implementation in the field. This study aims to develop Scratch-based learning media to improve children's understanding of numbers and shapes in early childhood in Nabire Regency, Central Papua. The research method used is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The results of the analysis show the need for interactive media that is suitable for the characteristics of early childhood. The developed media is designed with attractive visuals, supporting audio, and a simple interface so that it is easy to use. Implementation in early childhood education institutions proves that children are more active, enthusiastic, and find it easier to understand the concepts of numbers and shapes through a game-based learning approach. The evaluation results show that this educational media is effective, in line with the learning scenario, and can be an innovative alternative to improve the quality of early childhood education in Nabire.